Peranan Kuliah Kerja Nyata dalam Pengembangan Kompetensi Mahasiswa: Studi Kasus Mahasiswa KKN Universitas Muhammadiyah Tapanuli Selatan di Desa Sinyior, Kecamatan Angkola Selatan - Afifah, Nur; Sukatno, Sukatno; Pratiwi, Puji; Saragih, Mawaddah; Alvionita, Nora; Mubaroq, Taufik; Dalimunthe, Khairun Nisa (Universitas Islam Sumatera Utara, 2025)
The Community Service Program (KKN) serves as a vital platform for applying academic knowledge and technology in real social settings, fostering students’ intellectual, social, and personal competencies. This study aims to examine the role of KKN in developing students’ competencies during their community engagement in Sinyior Village, South Angkola. Using a qualitative descriptive method, data were collected through observation, interviews, and documentation involving both participating students and community members. The findings reveal that KKN plays a substantial role in enhancing students’ social sensitivity, communication skills, teamwork, and adaptability through direct involvement in community empowerment activities. The interaction between students and local residents fosters a mutual exchange of knowledge and values, contributing to the improvement of students’ emotional intelligence and problem-solving abilities. Therefore, the KKN program not only strengthens the university’s role in community development but also functions as a transformative learning experience that supports human resource quality improvement in higher education.